TOWARD GOOD PRACTICE OF SUPPLY CHAIN MANAGEMENT A COMMUNITY SERVICE AT SUSU MBOK DARMI BOGOR INDONESIA - Yuary Farradia; Salmah Salmah (International Journal of Engagement and Empowerment, 2023)
Delivering a supply chain good practices might ensure goods and services reach consumers using the means and methods readily available in the workplace environment. To achieve a good supply chain management, it is a need to come across an excerpt of delivering the right product, in the right quantity, to the right people, at the right place and time, at the lowest possible cost. Good supply chain management is indeed required by any services industry such as commercial drinks services outlet. Susu Mbok Darmi provides commercial various milk drinks outlet, located at modern location, like mall and individual outlet location. A community service to enhance the knowledge toward good supply chain management was conducted to Susu Mbok Darmi team in particular its supply chain, purchasing and operation department. The activity was done in the form of workshop based on the preliminary observation and in-depth interview to identify the problem of current supply chain management. The result of this community service was an additional knowledge of best practice toward good supply chain management. Participants were successfully learned about the role of Procurement versus Purchasing, Strategic Sourcing, Contract Management and Materials Inventory Management